Odpowiedzi

Najlepsza Odpowiedź!
2010-02-25T20:17:22+01:00
A) 2x+3_5 = 2-x_3 - x *5
2x+3=10x/3-5x *3
6x+3= 10x - 15x
3=-11x /-11
x= -0,(27)

b) x+1_2 - x-1_3 = 1_4 *6
x+1/2 *6 - x-1/3 *6 = 3/2
3x+3- 2x-2=3/2
x=3/2+1
x=2.5

c) 4x+7_2 - 5x-1_6 = x+5 *6
12x+21-5x-1=6x+30
x=10

d) x+5_4 - 2x+1_8 = 1_2(2-x) *8
2x+10-2x-1=8-4x
4x=-1 /4
x= -0.25

2010-02-25T20:44:34+01:00
A) 2x + 3 _ 5 = 2 - x _ 3 - x/razy 15
30x + 9 = 30 - 5x - 15x
30x + 5x + 15x = 30 - 9
50x = 21/ :50
x = 0,42
b)
x + 1_2 - x - 1_3 = 1_4 / razy 12
12x + 6 - 12x - 4 = 3
12x -12x = 3 -6 + 4
0 = 1 - chyba źle przepisałeś

c)
4x+7_2 - 5x-1_6 = x+5
4x - 5x - x = 5 - 7_2 + 1_6
-2x = 5 - 7_2 + 1_6 / razy 12
- 24x = 60 - 42 + 2
- 24x = 20 / : (-24)
x = 0,8(3)

d)
x+5_4 - 2x+1_8 = 1_2(2-x)
x - 2x + 0,5x = 1 - 1_8 - 5_4
- 0,5x = 1 - 1_8 - 5_4 / razy 8
-4x=8 - 1 - 10
- 4x = - 3 / : (-4)
x = 0,75